A symptom-based approach to treatment of psychosis in autism spectrum disorder. Issue 1 (January 2018) - Bell, Victoria; Dunne, Henry; Zacharia, Tharun; Brooker, Katrina; Shergill, Sukhi
Summary: The optimal management of autism with psychosis remains unclear. This report describes a 22-year-old man with autism and psychosis who was referred to a tertiary-level specialist psychosis service, following a 6-year history of deterioration in mental health starting around the time of sitting GCSE examinations and an episode of bullying at school. We describe the individualised symptom-based approach that was effective in his treatment. Declaration of interest: The authors declare no conflict of interest.